O Cariri e os processos de valorização da sua cultura popular - Otília Aparecida Silva Souza (2017)
This work analyzes the strategies and discourses produced by the State, cultural centers, academies and intellectuals, in order to identify the Cariri region of Ceará (especially the cities of Crato and Juazeiro do Norte) as 'the privileged space of manifestations of popular culture' in Ceara. The idea of realizing it arose from the need to investigate the reasons that gave rise to a feeling of appreciation of popular manifestations of these cities by the State and some institutions, from the year 2003 - a period in which a large number of researchers, artists, entrepreneurs, financial institutions and governments (state, municipal and federal), have now given special attention to this segment of culture in the Cariri region. For its development, the vast field of popular manifestations is delimited and prioritizes popular art as an object of investigation which is understood here as 'the artistic works performed by the people in the field of plastic arts'. The research identifies, therefore, which processes trigger the valorization of the popular in Cariri, analyzing the submerged power relations in the discourses, images and political actions engendered to direct the form of apprehension of the cultural manifestations and to reaffirm the importance of them to the detriment of other expressions - cultural, political and artistic of the Region.